Peran Kepala Sekolah Sebagai Pemimpin Pembelajaran Dalam Membangun Sekolah Berkualitas Berdasarkan Teori Weber’s 1996 - yogi wiratomo; Muhyidin, Mohammad; Karim, Abdul; Japar, Muhammad; Herdiati, Dian (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2024)
This article examines the role of principals as instructional leaders based on Weber's theory (1996), which emphasizes five main dimensions in instructional leadership: school mission, curriculum and instruction management, learning climate, support for professional development, and monitoring and evaluation of learning. The study uses a qualitative approach and literature review to identify concrete steps that principals can take to build a quality educational environment that is responsive to the needs of students and the community. The findings indicate that implementing these five dimensions plays a crucial role in improving student learning outcomes and teaching effectiveness in schools. Principals who can effectively manage pedagogical, managerial, and social competencies can create a conducive learning climate and foster collaboration. This article recommends that principals strengthen their data analysis skills, encourage continuous professional development, and involve the entire school community in data-driven decision-making to achieve more optimal educational goals.